Pengaruh Beban Kerja terhadap Kinerja Karyawan PT. Nutrifood Kota Jambi - Rohayani Rohayani (Science of Management and Students Research Journal (SMS), 2019)
The research aims to find out and analyzed the workload and performance of employees of pt nurtifood jambi city, subsequently also to find out and analyzed how the workload on the performance of employees of pt nutrifood jambi city.Data collection method was done by distributing questionaires to 50 respondents who became employess in PT Nutrifood Jambi City. The questionnaires was mode based on workload indicator employees answer count using likert scale. And tabulated to be analyzed using range of scale simple linear regression. Simple linear regression statistic analysis was performad using SPSS version 22 statistic program. Based on scale range analysis it’s cocluded that employees workload and performance in PT Nutrifood Jambi City. Were good, so that in sample linear regression with regression formula of  Y = 14,409 + 0,470 X . it means performance valve will increases 0,470 if workload increases with one valve. Regression valve was  strengthen by determination R squere valve of 19,4 % . Valve in t- hypothesis analysis  was 3.579 which bigger that t table (2,011) based on the valve, H1 was accepted an Ho was rejected that means was workload has significant influenced to employees performance in PT Nutrifood Jambi City. Keywords : workload, performance of employee